Design and Development E-Mading System For Information Students - Farell, Geovanne; Novid, Igor; Rahmadika, Sandi (Universitas Trilogi, 2022)
This study aims to facilitate the provision of information and reduce the amount of paper use in the Department of Electronics Engineering, Faculty of Engineering, Padang State University. With the large amount of paper used to provide information on conventional e-mading, it causes too much paper to be wasted and not too effective in providing information. With the large amount of paper wasted also causes inefficient time. Because too much information and announcements reported to the Electronics Engineering Department cannot be managed by admin in the Department of Eletronics, Faculty of Engineering, Padang State University. Therefore, for now there is a need for a digital madding to manage information and reduce the amount of paper usage. There are 2 methods used in this study are Data Collection Methods and System Development Methods. This Data Collection Method uses interview and observation techniques, while the System Development Method uses USDP. In this study using the USDP method, where this method can do an object-oriented software development, design and analysis of software design using the UML approach (Unifed Modeling Language)